Innovating Democracy? - Thorsten Thiel; Sebastian Berg; Niklas Rakowski; Veza Clute-Simon (Weizenbaum Journal of the Digital Society, 2023)
The article concerns the case of #WirVsVirus, a civic hackathon organized in reaction to the COVID-19 pandemic and officially endorsed by Germany’s federal government. It aims to address the normative implications of this politically oriented technological format. Specifically, it asks how civic hackathons formulate and negotiate different political representation claims. Our analysis shows that the hackathon constituted a successful representative claim on behalf of civic tech initiatives vis-à-vis the administrative state. While this claim primarily concerned establishing a new format for efficient and subsidiary problem-solving in the wake of the crisis, the hackathon’s participatory promises have only been partially fulfilled. The hackathon was rather open to input from civil society, enabling it to attract substantial public interest. Nonetheless, its technological-organizational structure and competitive, solution-oriented procedures meant that decision-making power remained largely with the hackathon’s organizers.